The Influence of the MalMath Technological Tool on the Learning of Quadratic Equations among Preparatec Tecsup Students in Lima - Retamozo Sanchez, Luis Alberto (2026)
Educational processes that particularly benefit from the use of instructional technologies are those involving extensive calculations and the construction of graphs of varying complexity, such as mathematics. In this context, the present study examines the influence of the MalMath technological tool on the learning of quadratic equations among students enrolled in the Heavy Machinery Management and Maintenance program at Preparatec Tecsup. A quasi-experimental design was employed, with a sample of 50 students divided into a control group and an experimental group, using pre-test and post-test measurements. The results indicate that the pre-test did not act as a significant covariate influencing post-test outcomes. Consequently, the findings demonstrate that the use of the MalMath tool had a statistically significant positive effect on students’ learning of quadratic equations in introductory university-level mathematics courses.